2013
DOI: 10.3109/14767058.2013.861415
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IL-17, IL-35, interferon-γ, SOCS3 and TGF-β levels in pregnant women with preeclampsia, and their relation with severity of disease

Abstract: Increased IFN-gamma/TGF-beta production and reduced IL-35/IL-17/SOCS3 production in preeclamptic women may lead to less cytokine inhibitory activity in PE, which may account for the increased proteinuria and blood pressure in PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…Multiplex bead array technology has a high dynamic range, and it may not be optimal for evaluating analytes with very low concentration. In a recent study, IL-17 levels were determined in plasma samples of 40 preeclamptic and 40 normotensive pregnant women with ELISA (Ozkan et al 2014). The authors found lower IL-17 levels in the preeclamptic group.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex bead array technology has a high dynamic range, and it may not be optimal for evaluating analytes with very low concentration. In a recent study, IL-17 levels were determined in plasma samples of 40 preeclamptic and 40 normotensive pregnant women with ELISA (Ozkan et al 2014). The authors found lower IL-17 levels in the preeclamptic group.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also has an important role in induction of the protective immune response against extracellular bacteria or fungal pathogens at mucosal surfaces (608, 611623). Th17 cells seem to participate in successful pregnancy processes and can be lower in PE (624626), although more studies show them as higher (599, 627635) or unchanged (636, 637). One interpretation, consistent with the present thesis, is that the antimicrobial effects of placental IL-17 relative to T reg cells are compromised during PE (599, 633, 638).…”
Section: Effects Of Lps and Other Microbial Antigens On Disrupting Trmentioning
confidence: 99%
“…They observed significantly decreased SOCS-3 levels in preeclamptic women compared to that in normotensive controls. Ozkan et al [12] observed negative correlation between maternal plasma SOCS-3 levels and severity of PE. Wang et al [13] reported reduced SOCS-3 expression in leukocyte and vessel endothelium of preeclamptic women compared to those in normotensive pregnants.…”
Section: Are There Any Differences Between Preeclamptic and Healty Prmentioning
confidence: 98%
“…Suppressor of cytokine signaling-3 (SOCS-3) plays an important role in negative regulation of inflammatory response [11]. Decreased serum and placental SOCS-3 levels in preeclampsia may account for the increased inflammatory response in PE [12][13][14]. We hypothesize that both of MFG-E8 and SOCS3 levels may decrease or increase either being result or reason of PE.…”
Section: Introductionmentioning
confidence: 99%